MODERN PROBLEMS OF ANTHROPOGENIC LANDSCAPES - Borodina Marina Rostislavovna (Modern American Journals, 2025)
What is "landscape design"? Is it conceptual art or merely landscaping and beautification? What role does creativity play in the professional activities of landscape designers and landscape architects? This article explores the challenges related to modern landscape types—residential, anthropogenic, and cultural. It also examines renovation methods, strategies for creating a sustainable biosphere, and secondary reconstruction of disturbed anthropogenic landscapes. Finally, the study discusses pathways toward "green architecture" as an integral part of ecological urban planning.
Keywords: Park architecture, landscape design, anthropogenic, renovation, sustainability, green architecture.